Public order as an exclusive premise of the police force in Latin America: A systematic review (Journal of Namibian Studies : History Politics Culture, 2023)
This systematic review aims to analyze public order as an exclusive premise of the police force in Latin America. In order to achieve this goal, a selection of relevant scientific studies was carried out. Through a critical analysis of the scientific literature, the main findings, methodologies, and approaches used in the selected studies were thoroughly examined. The different aspects related to the maintenance of public order were explored, such as control strategies, crime prevention, riot management, and police-community interaction. The results obtained in this systematic review provide a comprehensive and updated view on the importance of public order as a fundamental foundation for the proper functioning of police forces in a democratic society based on the rule of law. In addition, it highlights the need for adequate and proportional use of force by police forces, following the principles of legality, impartiality, and respect for human rights.